Role of Bupropion in the Management of Internet Gaming Disorder: A Systematic Review - Suryadarma , Antonius Yansen; Trisna, Irwan (Basic and Applied Nursing Research Journal, 2023)
This systematic review aims to summarize the role of bupropion in the management of internet gaming disorder (IGD) patients. Five electronic databases were searched without date restrictions until September 10, 2021. Four studies with a moderate risk of bias were included. Compared to escitalopram, bupropion showed better improvement in reducing addictive use of online gaming and IGD severity (low certainty). Compared with placebo or no treatment, bupropion was better in reducing addictive use of online gaming, IGD severity, and the total time of online game playing (low to moderate certainty). The combination of bupropion with cognitive behavior therapy (CBT) was superior to bupropion alone in reducing the addictive use of online gaming and the total time of online game playing (low certainty). Bupropion may be effective in improving IGD symptoms. However, there is an evident need for more extensive randomized controlled trials (RCTs) with better methodology and longer follow-up before more conclusions can be drawn.